RISK OF DEVELOPMENT OF DISEASES WITH TEMPORARY DISABILITY IN WORKERS OF THE MINING AND METALLURGICAL INDUSTRY OF UKRAINE - Kovalchuk, T.A.; Oriekhova, O.V.; Pavlenko, O.I. (World of Medicine and Biology, 2019)
The purpose of this study was risk assessment of morbidity with temporary disability among workers engaged in mining and processing of iron ore in the mining and metallurgical industry of Ukraine. The risk of developing common diseases in workers of mining and metallurgical industry is lower than in the control group and equals to 0.127 for underground extraction of iron ore, 0,173 for the open-pit mining of iron ore and 0,161 for metallurgical production, and the ratio of the chances of Contracting an occupational disease (OR) is 0,0516, 0,0061 and 0,041 respectively, which correlated with working conditions. The conducted studies prove the need to calculate an individual safe working life and open the prospects for further scientific research aimed at developing and implementing an effective occupational risk management system.
Keywords: working conditions; morbidity; occupational risk; mining and metallurgical industry